2016
DOI: 10.4103/1119-3077.188709
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive use, prescription patterns, and cost of medications in a Teaching Hospital in Lagos, Nigeria

Abstract: Antihypertensive prescription pattern was in accordance with the seventh report of Joint National Committee on Prevention, Detection, Evaluation, and Treatment of high blood pressure. Community-based insurance scheme should be encouraged and effective implementation of integrated noncommunicable diseases screening into the primary health care services would be helpful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
46
3
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 16 publications
7
46
3
3
Order By: Relevance
“…In our sample, a small proportion 22.5% of the patient was treated with monotherapy, this is supported by reports from Nigeria 2.5% [44], 20% [45] and India 27.7% [22]. In contrast, an Indian study [46] reported most CVD patients to be treated with monotherapy and Patel et al [47] reported the use of monotherapy to treat diabetic patients.…”
Section: Discussionsupporting
confidence: 82%
“…In our sample, a small proportion 22.5% of the patient was treated with monotherapy, this is supported by reports from Nigeria 2.5% [44], 20% [45] and India 27.7% [22]. In contrast, an Indian study [46] reported most CVD patients to be treated with monotherapy and Patel et al [47] reported the use of monotherapy to treat diabetic patients.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, this could be the reason to have a tendency to prescribe an ARB, even though ACE inhibitors are more affordable. Unlike the present study, ARBs were the least chosen drugs in studies conducted in Nigeria and Bahrain [12,15]. This may be due to the high cost of the newer ARBs.…”
Section: Pharmacotherapy Of Hypertension In North Cyprus фармакотерапcontrasting
confidence: 63%
“…In addition, unlike the guidelines according to the ATC-2 subclassification, diuretics were the fourth chosen drug whereas according to the ATC-5 subclassification a high-ceiling diuretic, furosemide was the third-chosen drug in hypertension treatment. In a study conducted in Turkey and in Nigeria, diuretics was the most preferred drugs [15,16]. In this study, it was observed that the most common prescribed diuretics were the highceiling diuretics and potassium-sparing agents.…”
Section: Pharmacotherapy Of Hypertension In North Cyprus фармакотерапmentioning
confidence: 72%
See 1 more Smart Citation
“…13 In Nigeria, adopting a general guide on cost-effective prescribing in the treatment of hypertension has not been possible, despite the efforts made by some researchers in the past. [14][15][16][17][18][19]3 This is partly due to the fact that prices of antihypertensive drugs are not uniform throughout the country, depending on the sources from which the drugs are procured, and partly because the perspectives of these pharmacoeconomics studies also differ from one another.…”
Section: Introductionmentioning
confidence: 99%